I'm trying to integrate this function wrt $x$, substituting $x = a \tan \theta$

$$ \int \sqrt{x^2+a^2} dx = a^2 \int \frac {d\theta}{\cos^3\theta} = $$

$$= a^2 \cdot \frac 12 \left( \tan\theta \sec\theta + \ln\lvert \tan\theta + \sec\theta \rvert \right) = \frac 12 \left( x \sqrt{a^2 + x^2} + a^2 \ln \left| \frac x a + \frac{\sqrt{a^2+x^2}}{a} \right| \right)$$

But WolframAlpha says it should be

$$= \frac 12 \left( x \sqrt{a^2 + x^2} + a^2 \ln \left| x + \sqrt{a^2+x^2} \right| \right)$$

What am I doing wrong?


2 Answers 2


Notice, your result is correct because adding or subtracting a constant will make no difference in the result. This can also be obtained using integration by parts

let $$I=\int \sqrt{x^2+a^2}\ dx\tag 1$$ $$I=\int \underbrace{\sqrt{x^2+a^2}}_{I}\cdot \underbrace{1}_{II}\ dx$$ using integration by parts $$I=\sqrt{x^2+a^2}\int \ dx-\int\left(\frac{d}{dx}(\sqrt{x^2+a^2})\cdot \int 1\ dx\right)\ dx$$ $$I=x\sqrt{x^2+a^2}-\int\left(\frac{2x}{2\sqrt{x^2+a^2}}\cdot x\right)\ dx$$ $$I=x\sqrt{x^2+a^2}-\int\left(\frac{x^2}{\sqrt{x^2+a^2}}\right)\ dx$$ $$I=x\sqrt{x^2+a^2}-\int\frac{(x^2+a^2)-a^2}{\sqrt{x^2+a^2}}\ dx$$ $$I=x\sqrt{x^2+a^2}-\int \sqrt{x^2+a^2}\ dx+a^2\int\frac{1}{\sqrt{x^2+a^2}}\ dx$$ from (1) $$I=x\sqrt{x^2+a^2}-I+a^2\int\frac{1}{\sqrt{x^2+a^2}}\ dx$$ $$I=\frac{1}{2}\left(x\sqrt{x^2+a^2}+a^2\int\frac{1}{\sqrt{x^2+a^2}}\ dx\right)\tag 2$$

Now, let $x=a\tan \theta\implies dx=a\sec^2\theta\ d\theta$ $$ \int\frac{1}{\sqrt{x^2+a^2}}\ dx= \int\frac{1}{\sqrt{a^2\tan^2\theta+a^2}}(a\sec^2\theta \ d\theta)$$ $$=\int \sec\theta\ d\theta=\ln|\sec\theta +\tan\theta|$$

$$=\ln\left|\tan\theta+\sqrt{\tan^2\theta+1}\right|=\ln\left|x+\sqrt{x^2+a^2}\right|+c$$ setting the value in (2), we get $$I=\frac{1}{2}\left(x\sqrt{x^2+a^2}+a^2\ln\left|x+\sqrt{x^2+a^2}\right|\right)$$


$$\frac 12 \left( x \sqrt{a^2 + x^2} + a^2 \ln \left| \frac x a + \frac{\sqrt{a^2+x^2}}{a} \right| \right)\\=\frac 12 \left( x \sqrt{a^2 + x^2} + a^2 \ln \left| x + \sqrt{a^2+x^2} \right| \right)-\frac{a^2\ln|a|}{2} $$


$$\frac 12 \left( x \sqrt{a^2 + x^2} + a^2 \ln \left| x + \sqrt{a^2+x^2} \right| \right)$$

are different by a constant, so nothing is wrong!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.